Pengaruh Kompetensi, Independensi, Skeptisisme Profesional, Dan Rotasi Audit (Studi Pada Akuntan Publik Seluruh Indonesia) - Rheza Chandra Putra; Dini Rosdini; Cahya Irawady (JAF (Journal of Accounting and Finance), 2023)
The purpose of this research to determines the effect and correlation between Independence variable (X) that is Competence (X1), Independence (X2), Professional Skepticism (X3), and Audit Rotation (X4) to Dependent variable (Y) that is Audit Rotation (Y). Population of this research is All of Public Accountant in Indonesia. Sampling technique that used in this research was Cochran Sampling method. This research was obtained data from questionnaires that distributed to 238 Public Accountant in Bandung City, Centre Jakarta, West Jakarta, East Jakarta, North Jakarta, South Jakarta, and Bekasi City. Research method that used in this research was Path Analysis with SPSS 27 as statistics engine. The Results show that Competence (X1), Independence (X2), Professional Skepticism (X3), and Audit Rotation (X4) simulaneously has effect and correlation to Audit Rotation (Y). Keywords: Audit Quality; Audit Rotation; Competence; Independence; Professional Skepticism